Ethnophaulisms from a translational perspective - Kubiak, Paweł (Glottodidactica, 2017)
The subject of this paper is the translational challenge which is translating linguistic representations of national stereotypes, depicted on the examples of ethnonyms of a pejorative overtone, used by representatives of one nation towards another, such as: szwab in Polish and Piefke, Tschusch and Katzelmacher in German. The claim of the article is that the transfer of ethnophaulisms is to be based on their duality as assertive and expressive speech acts.